Determination of the Stress Responses and Mineral Compositions of Some Common Wheats (Triticum aestivum L.) under Salt Treatment - Hasan CAN; Mehmet HAMURCU; Sait GEZGIN; Erdogan Esref HAKKI (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
The aim of this research is to evaluate and analyze the influence of different degrees of salt stress on the tolerance of Australian wheat lines having characteristics derived from wild types in comparison with a local cultivar well–adapted to Anatolian conditions under controlled conditions. In the research, the two lines, namely AU5924 and AU5907, adapted to Australian conditions harbor HKT1;4 and HKT1;5 loci and Bayraktar 2000 cultivar used as genetic material. In our study, a trial plan with four replicates and two salt treatment doses (0 mM control group and 200 mM stress group) was designed. The samples were collected for elemental analysis, measuring physiological parameters as well as determining proline content after the appearance of stress symptoms. In this respect, (K), known to play an important role in enhancing stress tolerance, was found to be higher in HKT–containing lines in comparison to Bayraktar 2000. HKT genes could improve the production of Anatolian varieties. While the dry weight of the genotype Bayraktar 2000 was higher than the lines checked, the proline content of line 5907 was lower and the potassium and (K/Na) ratio decreased. These parameters effectively increased the dry weight under salt stress. However, the line 5907 demonstrated the best tolerance among all analyzed genotypes.